(untitled) (Biological Sciences - PJSIR, 2025)
The butterfly house at the botanical garden in Lahore, Punjab, Pakistan, serves as a sanctuary for a diverse array of butterfly species. This study was conducted from September 2022 to May 2023, focusing on the butterfly species present in this sanctuary. A total of 24 species from three families Papilionidae, Pieridae and Nymphalidae were identified using standard identification literature. Specifically, 13 species belonged to the Nymphalidae family, 7 to Pieridae and 4 to Papilionidae. Nymphalidae was the most represented family, constituting 54% of the species diversity, followed by Pieridae (29%) and Papilionidae (17%). Notably, rare species such as the common blue bottle, common crow, paper kite, common windmill and chocolate pansy were observed. This research represents the first checklist of butterfly fauna in the Lahore botanical garden and underscores the need for further studies to comprehensively document the area’s butterfly biodiversity. This information is crucial for monitoring ecological trends and habitat conditions.